Study on Impact of Variation of Carbon Monoxide Concentration to Air Temperature at Simpang Lima, Banda Aceh - Rahimi .; Irhamni .; Nazli Ismail (PSI-Aceh, 2012)
Studies on impact of variation of carbon monoxide concentration to air temperature have been conducted at Simpang Lima, Banda Aceh. Objectives of this research are to determine the level of emissions of carbon monoxide from motor vehicles, to study the fluctuations of air temperature in the area, and to analyze the impact of increasing carbon monoxide concentration to the air temperature at Simpang Lima Banda Aceh during 2010. Concentration of carbon monoxide and air temperature were recorded by Air Quality Monitoring System (AQMS) device installed at Simpang Lima Banda Aceh. The result shows that carbon monoxide concentration increases as well as number of vehicles passing the area. Change of the concentration in the air is also influenced by temperature variability in the research area. For the temperature, beside affected by carbon monoxide concentrations are also influenced by weather factors such as solar radiation, wind speed and precipitation. However, levels of carbon monoxide concentration at Simpang Lima, Banda Aceh are considerably safe for the environment, i. e. less than 100 ppm.